Neuronal basis and diverse mechanisms of pathogen avoidance in Caenorhabditis elegans - Lei, Ming; Tan, Yanheng; Tu, Haijun; Tan, Weihong (Frontiers in Immunology, 2024)
Pathogen avoidance behaviour has been observed across animal taxa as a vital host-microbe interaction mechanism. The nematode Caenorhabditis elegans has evolved multiple diverse mechanisms for pathogen avoidance under natural selection pressure. We summarise the current knowledge of the stimuli that trigger pathogen avoidance, including alterations in aerotaxis, intestinal bloating, and metabolites. We then survey the neural circuits involved in pathogen avoidance, transgenerational epigenetic inheritance of pathogen avoidance, signalling crosstalk between pathogen avoidance and innate immunity, and C. elegans avoidance of non-Pseudomonas bacteria. In this review, we highlight the latest advances in understanding host-microbe interactions and the gut-brain axis.